IDDF2022-ABS-0278 Autophagy activators alleviate DSS-induced colitis by regulating gut microbiota. (2nd September 2022) - Guo, Xue; Xu, Haoming; Xu, Jing; Huang, Chen; Nie, Yuqiang; Zhou, Youlian
Abstract : Background: Inflammatory bowel disease (IBD) is characterized by relapse and remission alternately. Autophagy plays a key role in maintaining gut homeostasis, regulating the gut ecology, and defending against enteric pathogens. This study aims to observe the effect of autophagy and how it alters the gut microbiota on colitis mice. Methods: Twenty-four Balb/c mice aged 6–8 weeks were randomly divided into four groups, and rapamycin (RAPA) and chloroquine (CQ) were used to treat colitis mice. The body weight, disease activity index (DAI), and colon length of mice were observed, respectively. The relative expression of inflammatory cytokines in colon tissue was detected by qPCR, and the gut microbiota of fecal was tested by 16S rRNA sequencing. Results: After RAPA intervention, the DAI of mice was decreased (IDDF2022-ABS-0278 Figure 1A. Disease activity index (DAI) dynamics across each group), the shortened colon length was improved (IDDF2022-ABS-0278 Figure 1B-C. The general appearance of the colon of mice in each group and the colon length, ), IL-6 and TNF-α levels were decreased (IDDF2022-ABS-0278 Figure 1D-E. The levels of serum IL-6 and TNF-α) and colonic pathological scores in mice with colitis were decreased significantly (IDDF2022-ABS-0278 Figure 1F-G. Colonic tissues stained with H&E (200×, 400×) and colonic pathology score). Otherwise, under CQ intervention, no symptom of colitis was improved. 16S rRNA sequencing found that the RAPA intervention group increased the α diversity of the microbiota (IDDF2022-ABS-0278 Figure 1H. ACE index) and had significant differences in microbiota structure with the DSS group (IDDF2022-ABS-0278 Figure 1I-J. Principal Coordinate Analysis (PCoA)). Comparing with the DSS group, Alistipes, stenotrophomonas, Lactobacillus are increased in the RAPA group, otherwise, Ileibacterium, unidentified-Ruminococcaceae, Anaerotruncus are decreased in the CQ group (IDDF2022-ABS-0278 Figure 1K. Relative abundance of taxa at the genus level). Conclusions: Autophagy activators can alleviate inflammation and colon pathology in colitis mice. Autophagy activators may change the structure of intestinal microbiota, exerting an anti-inflammatory effect on enteritis mice. This study provides evidence for further proof that autophagy activators improve colitis, explores the mechanism of autophagy activators in the intestinal microenvironment, and provides new targets for the treatment of inflammatory bowel disease.